Improving Elementary School Students’ Learning Outcomes in Islamic Religious Education Using the STAD (Student Teams-Achievement Divisions) Cooperative Learning Model - Hasanah Hasanah; Pasma Candra (Academia Edu Cendekia Indonesia (AEDUCIA), 2026)
Background: Low student learning outcomes in Islamic Religious Education, particularly in Understanding Puberty, are influenced by the continued use of conventional, teacher-centered instructional methods that limit student engagement. Objective: This study aimed to improve students’ learning outcomes by implementing the Cooperative Learning model, specifically the STAD (Student Teams–Achievement Divisions) type, in Islamic Religious Education. Method: This research used a Classroom Action Research (CAR) design. The research subjects were 20 fourth-grade students at SD Negeri 12 Palembang. Data were collected through observations and achievement tests and analyzed using descriptive quantitative techniques. Findings: The findings showed a significant improvement in students’ learning outcomes following the implementation of the STAD model. Mastery learning increased from 30% in the pre-cycle to 50% in Cycle I, 80% in Cycle II, and 99% in Cycle III. In addition, students’ engagement and collaboration steadily improved throughout the learning cycles. Conclusion: The STAD Cooperative Learning model effectively enhances students’ learning outcomes and engagement in Islamic Religious Education. This model promotes an active, collaborative, and meaningful learning environment. Contribution: This study offers practical guidance for teachers in developing innovative instructional strategies for Islamic Religious Education and strengthens empirical evidence regarding the effectiveness of the STAD model in improving elementary school students’ learning outcomes.